Evaluasi Kinerja Simpang (Studi Kasus : Simpang Polsek Sukarame) - Purba, Daniel Bungaran; Purba, Aleksander; Michael (Fakultas Teknik Universitas Lampung, 2021)
The Polsek Sukarame Intersection is an intersection close to the Institut Teknologi Sumatera (ITERA) campus and the exit of Trans Sumatra toll gate. The increase in the volume of traffic in Bandar Lampung as well as the development of commercial areas around the intersection may cause traffic congestion so that it may cause problems in the future. Therefore an evaluation is needed to determine the feasibility of the performance of the Polsek Sukarame Intersection.This research aims to evaluate the performance of the intersection in 2020 by planning performance improvements. The planned intersection performance improvement is level. The main reference used in this research is PKJI 2014. This research uses primary data (environmental conditions and intersection geometry data) and secondary data (traffic flow on the intersection data). Primary data is obtained by direct observation, while secondary data comes from the data of a previous researcher. Based on the evaluation results, the Polsek Sukarame Intersection in 2020 is still feasible to operate according to the PKJI 2014 because the DJ (degree of saturation) value is <0.85. It is predicted that the degree of saturation will exceed 0.85 in 2033, so it requires performance improvements in a level manner. In general, the planned performance improvements include planning for widening approaches, roundabouts, and signalised intersection. The most optimum widening scheme of the approach is the combination scheme with the width of the Ryacudu approach of 10.00 m; Airan of 8.00 m; Senopati of 6.00 m; and Suhaimi of 10.00 m. Roundabout planning requires a minimum diameter of 30 m. It is recommended to use a 3-phase arrangement APILL junction with a widening approach. Cycle time is between 51-100 seconds. The maximum value of the degree of saturation is 0.40 and the maximum average delay of the intersection is 6.25 sec/veh, resulting in a service level indicator between indicators A and B. All these plans require sufficient land acquisition to facilitate the implementation of these plans.